Evaluation of Vehicles Transport Procedures on Board of KMP Lohoraung and KMP. Tarusi at Likupang - Biaro and Likupang – Melonguane Tracking, North Celebes Province - Rudy Sugiharto; Noor Sulistiyono; Bella Bidaswara (IWTJ : International Water Transport Journal, 2019)
The Ferry Port of Likupang is one of the ferry port located in North Sulawesi province, has a very strategic position and has a huge economic potential to support the local economy. In the security and safety of the transportation system highly favored as a form of good service delivery. Safety was shown not only to the service users, but also to the ship operator. As well as setting up and handling of cargo vehicles on board. The better regulation and vehicle handling on board the better the level of security and safety of vehicles in ship. Settings and cargo handling vehicles on the ship is good for the service user / owner of the vehicle, as well as for the security and safety of vehicles on board and are not harmful to the operator of the vessel that can be done by means of an approach based on the arrangement of the vehicle by placing a distance between the vehicle safe and mounting strap vehicle(Lashing) contained in the Ministry Of Transportation Regulation Number 115 of 2016 on procedures for the transport of vehicles on the vessel and Ministry Of Transportation Regulation Number 30 of 2016 on concerning the binding obligation on Ferry Transport